"Don't blame the shopkeeper!!": Food, drink and confectionery advertising and British Government market controls during the Second World War. (20th November 2017) - Hayes, Mick
Abstract : Purpose: The purpose of this paper is to illustrate the impact of zoning and pooling on brands, something not covered in depth in the historical literature. Also, the paper is intended to present research into how brands in the food, drink and confectionery industries during the Second World War used advertising in response to the government control of the market. Design/methodology/approach: This paper is based on a close reading and interpretation of food, drink and confectionery brands advertisements from the Daily Express and Daily Mirror newspapers across the Second World War. Building on the work by Burridge (2008), it explores different message strategies used by brands in response to shortages, zoning and pooling. Findings: While rationing has been discussed at length in the historical literature, zoning and pooling have not been. While brands provided information to their customers about rationing, shortages, zoning and pooling, the latter three also caused brands to apologise, look to the future and urge patience. Research limitations/implications: This study is based on the Daily Express and Daily Mirror from August 1939 to September 1945. Further research could explore other publications or the period after the war as control continued. Exploration of brand and agency archives could also provide more background into brands' objectives and decision-making. Originality/value: This is the first research to explore the impact of forms of control other than rationing on advertising during the Second World War.